PERAN MEDIA DIGITAL PUBLIK RELATION DJP DALAM KAMPANYE PAJAK (CONTENT ANALYSIS PADA AKUN YOUTUBE @DitjenPajakRI) - Novia Sri Falinda; Arianto Arianto; Imtiyaz Farras Mufidah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Digital media is now a strategic tool for government agencies in conveying messages and building relationships with the public. One of them is by using digital media (YouTube) as a means of information. This study aims to analyze the role of digital media Public Relations (PR) of the Directorate General of Taxes (DJP) in tax campaigns through the YouTube @DitjenPajakRI platform. This study uses a qualitative content analysis approach to campaign videos uploaded on the official DJP YouTube channel within a certain period of time. The results of the study show that PR DJP uses YouTube not only as an information medium, but also as an educational and persuasive tool in increasing public tax awareness. Campaign messages are packaged with an attractive visual style, a communicative narrative approach, and utilizing public figures to strengthen the impact of the message. In addition, interactions through comments and the number of views indicate quite high public participation. This study concludes that digital media, especially YouTube, has significant effectiveness in supporting PR DJP's communication strategy in socializing tax policies and obligations more widely and inclusively.Keywords: Digital Media, Public Relations, Tax Campaign, Directorate General of Taxes, Youtube.